2022
DOI: 10.1108/md-11-2020-1528
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation in extreme institutional contexts: the case of Palestine

Abstract: PurposeThis paper focuses on social innovation dynamics in extreme contexts where institutional volatility is deeply rooted and enduring. In other words, the authors focus their discussion on the challenges that social innovators are facing in their endeavor of solving wicked social problems within an extreme institutional environment. This research is guided by the following question: How does an extreme institutional environment influence social innovation processes?Design/methodology/approachThis qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 99 publications
(189 reference statements)
1
7
0
Order By: Relevance
“…Additionally, social innovation is not an established concept within the culture of CSOs and has yet to become institutionalized. Our analysis supports the findings of previous literature on social innovation (Morrar & Baba, 2022).…”
Section: From Knowledge Management To Social Innovation: Hinderingsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, social innovation is not an established concept within the culture of CSOs and has yet to become institutionalized. Our analysis supports the findings of previous literature on social innovation (Morrar & Baba, 2022).…”
Section: From Knowledge Management To Social Innovation: Hinderingsupporting
confidence: 91%
“…Social innovation (SI) offers an alternative to donor-aiddriven models and aid dependency, defined as an approach to satisfy social needs and generate social value (Borzaga & Bodini, 2012;Phills et al, 2008). However, for SI to be effective in Palestine, three barriers must be overcome, including a lack of culture for SI, negative competitiveness between CSOs, lack of coordination between donors and CSOs, and low capacity to innovate (Morrar & Baba, 2022).…”
Section: Social Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social influence (SI) is theorized in this study to address the challenges of various stakeholders in doing business (Morrar and Baba, 2022). The results showed that SI has a significant influence on SBMI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a large civil society sector is supposed to provide a favorable base for social enterprises. In fact, Morrar and Baba (2022) argues that this is even true for social innovation in extreme institutional contexts.…”
Section: The Mise Framework and Hypothesesmentioning
confidence: 99%